2016
DOI: 10.1177/0265407516644348
|View full text |Cite
|
Sign up to set email alerts
|

Chronic social exclusion and evidence for the resignation stage

Abstract: Experiences of social exclusion, including ostracism and rejection, can last anywhere from a few seconds to many years. Most research focused on short-term social exclusion, whereas virtually no empirical work has investigated the experiences of long-term social exclusion. Williams theorized that prolonged experiences of social exclusion (i.e., ostracism) would cause individuals to pass from the reflexive and reflective stages to the resignation stage characterized by the inability to recover threatened psycho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
96
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 130 publications
(107 citation statements)
references
References 38 publications
3
96
1
1
Order By: Relevance
“…However, a close inspection of the literature, viewed through the lens of the taxonomy, paints a different picture. Specifically, repeated rejection results in feelings of helplessness, unworthiness, submission, withdrawal, and avoidance of social interactions, described as “going into a little shell” (Riva, Montali, Wirth, Curioni, & Williams, ; Williams, ; Zadro, ). Thus, people who experienced repeated rejection use more disengaged antisocial responses to rejection (e.g., withdrawing from others) rather than engaged antisocial responses (e.g., attacking others; Figure ).…”
Section: Using the Bi‐dimensional Rejection Taxonomy To Frame Existinmentioning
confidence: 99%
“…However, a close inspection of the literature, viewed through the lens of the taxonomy, paints a different picture. Specifically, repeated rejection results in feelings of helplessness, unworthiness, submission, withdrawal, and avoidance of social interactions, described as “going into a little shell” (Riva, Montali, Wirth, Curioni, & Williams, ; Williams, ; Zadro, ). Thus, people who experienced repeated rejection use more disengaged antisocial responses to rejection (e.g., withdrawing from others) rather than engaged antisocial responses (e.g., attacking others; Figure ).…”
Section: Using the Bi‐dimensional Rejection Taxonomy To Frame Existinmentioning
confidence: 99%
“…Ostracism also threatens basic psychological needs, such as the need for belonging, self-esteem, control, and meaningful existence (Williams, 2009). Some individuals unfortunately experience ostracism chronically, and this experience can lead to feelings of alienation, depression, helplessness, and the feeling that life is meaningless (Riva, Montali, Wirth, Curioni, & Williams, 2016;Wesselmann, Ren, & Williams, 2015). Some individuals unfortunately experience ostracism chronically, and this experience can lead to feelings of alienation, depression, helplessness, and the feeling that life is meaningless (Riva, Montali, Wirth, Curioni, & Williams, 2016;Wesselmann, Ren, & Williams, 2015).…”
Section: Social Ostracismmentioning
confidence: 99%
“…Individuals seem to feel ostracized at the slightest cue (e.g., lack of eye contact, uncomfortable silence) and feel devalued socially by others (Böckler, Hömke, & Sebanz, 2014;Koudenburg, Postmes, & Gordijn, 2011;Wesselmann, Cardoso, Slater, & Williams, 2012;Wirth, Sacco, Hugenberg, & Williams, 2010). Some individuals unfortunately experience ostracism chronically, and this experience can lead to feelings of alienation, depression, helplessness, and the feeling that life is meaningless (Riva, Montali, Wirth, Curioni, & Williams, 2016;Wesselmann, Ren, & Williams, 2015). Prolonged feelings of loneliness, which often result from chronic ostracism, can have harmful effects on one's physical health and even shorten one's lifespan (Cacioppo & Patrick, 2008;Holt-Lunstad, Smith, Baker, Harris, & Stephenson, 2015).…”
Section: Social Ostracismmentioning
confidence: 99%
“…Moreover, the available data allowed us only to evaluate two (depression and unworthiness) of the four outcomes associated with the resignation stage, not considering alienation and helplessness (Williams, 2009). However, a similar procedure was adopted by Marinucci and Riva (2020), and past research showed that responses to the four outcomes are typically highly related (Riva et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this, experiencing prolonged social rejection may increase self‐isolation (Cuadrado, Tabernero, & Steinel, 2015) and depression rates, even resulting in suicidal ideation (Van Orden & Joiner, 2013). Recently, some evidence provided by Riva, Montali, Wirth, Curioni, and Williams (2017) supported the notion that chronic experiences of social exclusion are associated with higher levels of the resignation stage outcomes. Similar results have also been found in adolescent students, where social rejection is associated with social anxiety, isolation, and withdrawal (Inderbitzen et al, 1997).…”
Section: Introductionmentioning
confidence: 96%